الصكوك الإسلامية ودورها في تمويل المشاريع التنموية - بعض التجارب العالمية - لقوي, سعيدة; بورنان, مصطفى (جامعة الوادي - University of Eloued, 2022)
يهدف البحث إلى التعريف بالصكوك الإسلامية وإبراز أهميتها في تمويل المشاريع التنموية، خاصة أنها أدوات مالية بديلة عن السندات التقليدية التي تتعامل بالفوائد الربوية، حيث حققت الصكوك الإسلامية انتشارا واسعا في السوق العالمية، كما أنها تتميز بتعدد أنواعها من صكوك المشاركة والمضاربة إلى صكوك السلم والمرابحة والاستصناع وغيرها، مما أدى إلى زيادة قوتها كأداة من أدوات التمويل الإسلامي. والصكوك الإسلامية عبارة عن أوراق مالية، ويعتبر حاملو الصكوك الإسلامية هم أصحاب الأصول أو المشاريع الأساسية، حيث يتشاركون في الربح والخسارة. The research aims to introduce Islamic bonds and highlight their importance in financing development projects, especially that they are financial instruments alternative to traditional bonds that deal with usurious interests. As Islamic sukuk achieved wide spread in the global market, It is also characterized by its multiplicity of types, from Musharaka and Mudaraba sukuk to Salam, Murabaha, Istisna and others, which has led to an increase in its power as a tool of Islamic finance. Islamic sukuk are securities, and Islamic sukuk holders are the owners of the basic assets or projects, as they share in profit and loss.
Islamic Sukuk and its role in financing development projects Some international experiences
مقال
Keywords: صكوك إسلامية، تمويل إسلامي، مشاريع تنموية.; Islamic Sukuk, Islamic financing, development projects.